(untitled) (Sound Stage Screen, 2021)
A few years after the arrival of sound cinema in Italy, the technology of dubbing emerged as an optimal solution to transfer films across national borders. This seemingly simple artifice had enormous cultural and political ramifications transnationally. For example, in the early 1930s, dubbing became the only way to screen foreign films in Italy, and the fascist government transformed the technology into a filter to bolster national identity and limit internal and external "threats" such as local dialects, foreign words, and music. Thus, under Mussolini’s regime, a film’s soundtrack (including music, sounds, and noises) underwent significant manipulation once it crossed the Italian border. This article examines Italian dubbing in the 1930s through the lenses of national cinema and local production. Additionally, it aims to explore early soundtrack manipulations before the establishment of dubbing as a practice, as well as the nationalist roots of dubbing itself. Finally, by analysing archival documents, this study posits that dubbing was not merely a matter of mechanical translation, but also a locus of sound experimentation in a time of stagnation for Italian cinema. Investigating dubbing, a phenomenon so profoundly ingrained in Italian society, opens up new interpretations of Italian culture, political history, and film production from the 1930s throughout the twentieth century.